O teatro como um sistema de comunicação - Alves, Marcos Antônio [UNESP] (Universidade Estadual Paulista, Departamento de Filosofia, 2001)
Communication seems to be one of the artist's central objectives in the performance of a theatrical play. When that communication takes place, the artist and his public constitute a communicative system. In this work, the notion of communication system proposed by Shannon & Weaver is presented. This notion is related to the communicative system established in theatrical presentation. Subjects such as the following ones are investigated: which are the necessary components for the existence of communication between emitter and receiver?; when actors have in mind to transmit a certain message with a certain meaning and the audience interprets or understands this message in another way, can it be said that there was communication between them?; can the public communicate something to the actor, becoming thus the emitter?

A comunicação parece ser um dos objetivos centrais do artista na apresentação de uma peça teatral. Quando acontece essa comunicação, ele e seu público constituem, juntamente com certas características, um sistema comunicativo. Neste trabalho, expomos a noção de um sistema de comunicação proposta por Shannon e Weaver. Procuramos relacionar essa noção com o sistema comunicativo estabelecido na apresentação teatral. Investigamos questões como: quais os componentes necessários para a existência e possibilidade de comunicação entre emissor e receptor?; quando atores têm em mente transmitir uma certa mensagem com um significado determinado e o público a interpreta ou entende de outro modo, pode-se dizer que houve comunicação entre eles?; há a possibilidade de o público comunicar algo ao ator, tornando-se assim o emissor?
The theater as a communication system
Keywords: Communication; information; theater; communicative system; Comunicação; informação; teatro; sistema comunicativo